2014
DOI: 10.1002/jmv.23906
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus glycoprotein H genotype distribution and the relationship with hearing loss in children

Abstract: Cytomegalovirus (CMV) is a leading cause of congenital infection and a leading infectious cause of hearing loss in children. The ORF UL75 gene encodes envelope glycoprotein H (gH), which is essential for CMV entry into host cells and the target of the immune response in humans. However, the distribution of gH variants and the relationship between the viral genotype, viral load, and sequelae in children infected with CMV is debated. The UL75 genetic variation of CMV isolates from 42 newborns infected congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
3
26
1
Order By: Relevance
“…On the other hand, the investigation of Guo et al did not find any mixedgenotype infections, while Paradowska's investigation revealed mixed-genotype infections which were caused by both genotypes gH1 and gH2, comprising up to 25% of all cases of associated infections. 14 It is noteworthy that we found the highest gH2 HCMV distribution in the age group of newborns, whereas the highest rate of spread of gH1 HCMV was detected in the age group of >3 months. Excepting the one age group of 28De3 months, as age increased, the proportion of gH1 HCMV increased but the proportion of gH2 HCMV decreased.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…On the other hand, the investigation of Guo et al did not find any mixedgenotype infections, while Paradowska's investigation revealed mixed-genotype infections which were caused by both genotypes gH1 and gH2, comprising up to 25% of all cases of associated infections. 14 It is noteworthy that we found the highest gH2 HCMV distribution in the age group of newborns, whereas the highest rate of spread of gH1 HCMV was detected in the age group of >3 months. Excepting the one age group of 28De3 months, as age increased, the proportion of gH1 HCMV increased but the proportion of gH2 HCMV decreased.…”
Section: Discussionmentioning
confidence: 44%
“…19 Our results were in contrast to those of a study conducted by Paradowska et al in Poland, in which the authors found that HCMV infections in children were most commonly caused by the HCMV gH2 genotype. 14 In China, the findings of Guo et al for children residing in the city of Wuhan showed that 62 strains were of the gH1 genotype (60.8%, 62/102), whereas 40 strains were of the gH2 (39.2%, 40/102). In this study, we obtained similar results to Gao et al 20 These findings may indicate that gH1 HCMV is a major genotype in Chinese children.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study by Yu et al [24] , infants with UL55 genotype 1 and symptomatic CMV disease were diagnosed with CMV related liver disease more frequently. Two other recent studies by Paradowska et al [30] , [31] suggest that certain other CMV genotypes (UL73/gN and UL75/gH, respectively) may predict neurological dysfunction (gN4 genotype) or hearing loss and higher viral load (gH1 genotype) in congenitally and postnatally or unproven congenitally infected infants. Several studies on congenital CMV infection have suggested that blood and urine CMV loads may be important markers of CMV disease severity [24] , [25] , [31] [34] .…”
Section: Discussionmentioning
confidence: 93%
“…Two other recent studies by Paradowska et al [30] , [31] suggest that certain other CMV genotypes (UL73/gN and UL75/gH, respectively) may predict neurological dysfunction (gN4 genotype) or hearing loss and higher viral load (gH1 genotype) in congenitally and postnatally or unproven congenitally infected infants. Several studies on congenital CMV infection have suggested that blood and urine CMV loads may be important markers of CMV disease severity [24] , [25] , [31] [34] . It was recently documented that infants with postnatal CMV infection have significantly lower urine CMV load than infants with congenital CMV infection [35] .…”
Section: Discussionmentioning
confidence: 93%
“…These findings have spiked the interest of clinical virologists in identifying potential correlations between genetic variants and the pathogenic potential of different isolates. Several studies have found some evidence to correlate specific genotypes with disease outcome, investigating polymorphisms in the UL55 (glycoprotein B) (16)(17)(18)(19), UL73 (glycoprotein N) (20)(21)(22), UL75 (glycoprotein H) (23), UL144 (tumor necrosis factor alpha [TNF-␣]-like receptor) (24)(25)(26), and UL146 and UL147 (viral CXCL chemokines) (27,28) genes. Others, however, found no evidence of these relationships (29)(30)(31)(32).…”
mentioning
confidence: 99%